2016
DOI: 10.1155/2016/1584947
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anodal-tDCS on Event-Related Potentials: A Controlled Study

Abstract: We aim to measure the postintervention effects of A-tDCS (anodal-tDCS) on brain potentials commonly used in BCI applications, namely, Event-Related Desynchronization (ERD), Event-Related Synchronization (ERS), and P300. Ten subjects were given sham and 1.5 mA A-tDCS for 15 minutes on two separate experiments in a double-blind, randomized order. Postintervention EEG was recorded while subjects were asked to perform a spelling task based on the “oddball paradigm” while P300 power was measured. Additionally, ERD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Several studies have been investigating the effects of tDCS on neurophysiological parameters in healthy subjects. Izzidien et al (2016) found a significant increase in P3 power after application of anodal stimulation over the left motor cortex during a spelling task of an oddball paradigm. Keeser et al (2011) identified increased P2 and P3 amplitudes in a working memory n-back task after anodal tDCS.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 90%
“…Several studies have been investigating the effects of tDCS on neurophysiological parameters in healthy subjects. Izzidien et al (2016) found a significant increase in P3 power after application of anodal stimulation over the left motor cortex during a spelling task of an oddball paradigm. Keeser et al (2011) identified increased P2 and P3 amplitudes in a working memory n-back task after anodal tDCS.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 90%
“…Both the sham and tDCS sessions consisted of 15 minutes of stimulation [20,49]. The sham session consisted of current ramping up to 1.5mA over a 8s period, followed by a 5s fade out and 870s without any significant stimulation (just impedance control).…”
Section: Anodal-tdcs (A-tdcs) Application Protocolmentioning
confidence: 99%
“…Although, tDCS appears to have induced significant change in a few cognitive studies, inconsistencies still exist [19][20][21]. A growing body of literature [19,[21][22][23] suggests the importance that individual differences may have in moderating any influence that tDCS may have on cognitive functions [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, tDCS has been used to increase P300 response, decrease P300 latency, and generally enhance the accuracy of target detection in P300-BCI systems [8]. Anodal-tDCS has led to improved P300-BCI spelling performance in neurologically impaired subjects [9]. In sensorimotor rhythm-based BCIs, the orientation interactivity was changed through tDCS interaction during non-exogenous activities [10].…”
Section: Introductionmentioning
confidence: 99%